Dynamic characteristics and underlying mechanisms of renal blood flow autoregulation in the conscious dog - Just, Armin; Ehmke, Heimo; Toktomambetova, Lira; Kirchheim, Hartmut (American journal of physiology, 2001)
The time course of the autoregulatory response of renal blood flow (RBF) to a step increase in renal arterial pressure (RAP) was studied in conscious dogs. After RAP was reduced to 50 mmHg for 60 s, renal vascular resistance (RVR) decreased by 50%. When RAP was suddenly increased again, RVR returned to baseline with a characteristic time course (control;n = 15): within the first 10 s, it rose rapidly to 70% of baseline (response 1), thus already comprising 40% of the total RVR response. Thereafter, it increased at a much slower rate until it started to rise rapidly again at 20-30 s after the pressure step (response 2). After passing an overshoot of 117% at 43 s, RVR returned to baseline values. Similar responses were observed after RAP reduction for 5 min or after complete occlusions for 60 s. When tubuloglomerular feedback (TGF) was inhibited by furosemide (40 mg iv, n = 12),response 1 was enhanced, providing 60% of the total response, whereas response 2 was completely abolished. Instead, RVR slowly rose to reach the baseline at 60 s (response 3). The same pattern was observed when furosemide was given at a much higher dose (>600 mg iv; n = 6) or in combination with clamping of the plasma levels of nitric oxide (n = 6). In contrast to RVR, vascular resistance in the external iliac artery after a 60-s complete occlusion started to rise with a delay of 4 s and returned to baseline within 30 s. It is concluded that, in addition to the myogenic response and the TGF, a third regulatory mechanism significantly contributes to RBF autoregulation, independently of nitric oxide. The three mechanisms contribute about equally to resting RVR. The myogenic response is faster in the kidney than in the hindlimb.
Gesehen am 27.04.2021